Radar observations of the stratrosphere - implications for modelling - Woodman Pollitt, Ronald Francisco (1984)
During the last decade there has been a rapid development of radar techniques and installations for the study of middle atmospheric dynamics. Of special interest to this meeting are the capabilities of the technique to measure gravity wáves and turbulence. The outstanding advantage of the technique is the possibility of long continuous monitoring of the velocity field and turbulence morphology , with temporal resolutions of the order of one minute or better and a vertical spatial resolution of 30-150 meters.